Pengaruh Budaya Organisasi dan Disiplin Kerja terhadap Kinerja Pegawai Kantor Desa Kamasan Klungkung - Januarta, I Nengah; Wina Premayani, Ni Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study was made to determine the effect of organizational culture and work discipline on employee performance at the Kamasan Klungkung Village Office. The population in this study were employees of the Kamasan Klungkung Village Office, amounting to 36 people with a total sample of 36 respondents who were determined using the saturated sample method. Data was collected through observation, interviews, documentation, literature study, questionnaires. The data analysis technique used in this research is multiple linear regression analysis technique. Based on the results of the study, it can be seen that: Organizational culture and work discipline have a positive and significant effect partially and simultaneously on employee performance. Looking at the results of the research, the Kamasan Klungkung Village Office should conduct job training that can increase the insight and abilities of employees. Increasing employee insight and abilities will be able to encourage employees to be more creative and innovative in their work, besides that training can also be used as a forum for employees to start establishing communication with fellow co-workers which will create closeness and be able to establish good cooperation.